La informática y la comunicación como herramientas didácticas en el aprendizaje y su incidencia en la profesionalización del docente de educación básica, año 2014 - Vera Zambrano, Taimy Maribel (2015)
This research is aimed at solving a problem related to the little knowledge about the educational use of information and communications technology as didactic resources in the teaching-learning process in basic education, the object of the research is theoretically argues, is made a description of the application context, is proposed and validated a studio educational use of information and communications technology as didactic resources in the teaching-learning process in basic education, sharing and socializing with teachers, users of the alternative, substantiate its relevance and feasibility.